2017
DOI: 10.14295/oh.v23i3.1107
|View full text |Cite
|
Sign up to set email alerts
|

Optimal planting systems for cut gladiolus and stock production

Abstract: A study was conducted to elucidate the effect of different planting systems, videlicet (viz.) flat, ridge, and raised bed system on growth, yield and quality of gladiolus and stock. Corms of 'Rose Supreme' and 'White Prosperity' gladiolus and seedlings of 'Cheerful White', 'Lucinda Dark Rose Double' and 'Lucinda Dark Rose Single' stock were planted on different planting systems in individual experiments for each species. Gladiolus had similar good quality production irrespective of planting systems with numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Souza et al (2020) evaluating the cultivar White Goddess and Red Beauty found values of 15.3 and 12.6 florets per ear, respectively. Ahmad et al (2017) also found similar averages, with 12.6 florets per ear in different production systems. From this, it is observed that the stems harvested under the conditions of the experiment presented a higher amount than commonly found in the literature.…”
Section: White Friendship Red Beauty Jestersupporting
confidence: 67%
“…Souza et al (2020) evaluating the cultivar White Goddess and Red Beauty found values of 15.3 and 12.6 florets per ear, respectively. Ahmad et al (2017) also found similar averages, with 12.6 florets per ear in different production systems. From this, it is observed that the stems harvested under the conditions of the experiment presented a higher amount than commonly found in the literature.…”
Section: White Friendship Red Beauty Jestersupporting
confidence: 67%